Heterodyne polariscope for measuring the principal angle and phase retardation of stressed plastic substrates. (April 2021) - Lin, S.T.; Le, Q.H.; Chen, S.H.; Chen, C.S.
Highlights: An innovative heterodyne polariscope was introduced. It is capable of measuring the full-field principal angle and phase retardation of stressed substrates. Its validity and feasibility were verified using experimental results. The errors of the measured principal angle and phase retardation did not extend beyond 2.65° and 3.99°, respectively. Abstract: A heterodyne polariscope composed of a Zeeman laser, a half-wave plate, two quarter-wave plates, an analyzer, a photo-detector, and an x–y stage is proposed for determining the full-field principal angle and phase retardation of stressed plastic substrates. This paper introduces the configuration, measurement theory, and experimental setup of the polariscope. Additionally, this paper presents experiments as well as the results of these experiments. The experimental results show that the errors of the measured principal angle and phase retardation do not extend beyond 1.07° and 2.86°, respectively, and the results verify the validity and applicability of the proposed polariscope.